2008
DOI: 10.1677/joe-08-0325
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and mRNA expression analysis of two GH secretagogue receptor transcripts in orange-spotted grouper (Epinephelus coioides)

Abstract: GH secretagogue receptor (GHSR) is the receptor of ghrelin, a circulating GH-releasing and appetite-inducing hormone. In this paper, two Ghsr cDNAs, gpGhsr1a and gpGhsr1b, were identified and characterized in a teleost, the orange-spotted grouper (Epinephelus coioides). The gpGHSR1a is 1512 bp in length with an open reading frame (ORF) that encodes a protein of 383 amino acids with seven transmembrane (TM) domains, while the 1703 bp gpGHSR1b contains an ORF encoding for 303 amino acids with five TM domains. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 72 publications
1
20
0
1
Order By: Relevance
“…Similar to mammals, the GHS-R1a or GHS-R1a-LR transcripts have been found in various brain regions and peripheral organs, and the pituitary is the predominant expressing site for the ghrelin receptor isoforms in the majority of species, e.g. the channel catfish (Small et al 2009), chickens (Geelissen et al 2003, Tanaka et al 2003, Saito et al 2005, Richards et al 2006, Yamamoto et al 2008, and ducks (Nie et al 2009) for GHS-R1a, and in the black porgy , orange-spotted grouper (Chen et al 2008), and rainbow trout (Kaiya et al 2009b) for GHS-R1a-LR. An exception is frogs, where GHS-R1a mRNA is not detected in the pituitary but mainly in the brain (Kaiya et al 2011a).…”
Section: Distribution Of the Ghrelin Receptors And The Difference Betmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to mammals, the GHS-R1a or GHS-R1a-LR transcripts have been found in various brain regions and peripheral organs, and the pituitary is the predominant expressing site for the ghrelin receptor isoforms in the majority of species, e.g. the channel catfish (Small et al 2009), chickens (Geelissen et al 2003, Tanaka et al 2003, Saito et al 2005, Richards et al 2006, Yamamoto et al 2008, and ducks (Nie et al 2009) for GHS-R1a, and in the black porgy , orange-spotted grouper (Chen et al 2008), and rainbow trout (Kaiya et al 2009b) for GHS-R1a-LR. An exception is frogs, where GHS-R1a mRNA is not detected in the pituitary but mainly in the brain (Kaiya et al 2011a).…”
Section: Distribution Of the Ghrelin Receptors And The Difference Betmentioning
confidence: 99%
“…The brain is the tissue showing the second highest expression of the ghrelin receptor in fish and birds. In addition, the ghrelin receptor gene expression has also been detected in various amounts in more or less all peripheral tissues, such as the eyes, heart, thymus, liver, stomach, intestine, spleen, gill, gall bladder, muscle, kidney, head kidney, Brockmann bodies, skin, muscle, and gonads for fish , Chen et al 2008, Kaiya et al 2009a,b, Small et al 2009, Cruz et al 2010, the stomach and gonads, and to a lesser extent in the small and large intestines, adrenal gland, and kidney in frogs (Kaiya et al 2011a), and the heart, lung, thymus, liver, spleen, pancreas, gastrointestinal tract, adrenal gland, kidney, gonads, breast muscle, subcutaneous fat, leg muscle, abdominal fat, and uropygial gland in birds (Geelissen et al 2003, Tanaka et al 2003, Saito et al 2005, Richards et al 2006, Kitazawa et al 2009, Nie et al 2009). In birds, strain differences (Geelissen et al 2003, Tanaka et al 2003, Richards & McMurtry 2010) and a regionspecific expression in the gastrointestinal tract (Kitazawa et al 2009) have been reported.…”
Section: Distribution Of the Ghrelin Receptors And The Difference Betmentioning
confidence: 99%
“…In fishes, reverse transcription polymerase chain reaction (RT-PCR) has shown that ghrelin receptors are expressed in all brain regions (Chen et al 2008, Small et al 2009, Upton & Riley 2013, Sánchez-Bretaño et al 2015a, Zhang et al 2016. Furthermore, in situ hybridisation has revealed that the transcripts of two ghrelin receptors (ghs-r1a and ghs-r2a) are expressed in several brain regions, including the hypothalamus and preoptic lobes in zebrafish (Cruz et al 2010).…”
Section: Ghrelinmentioning
confidence: 99%
“…In all studied fish species to date, ghrelin receptors are expressed in the oxyntic cells and/or the mucosal and submucosal intestinal cells and in the hepatocytes (Chen et al 2008, Kaiya et al 2009a,b, Eom et al 2014, Cai et al 2015, Sánchez-Bretaño et al 2015a; Sánchez-Bretaño A, Blanco AM, Alonso-Gómez AL, Delgado MJ, Kah O & Isorna E, unpublished observations), suggesting that ghrelin may also act as a local signal that entrains the stomach and/or gut oscillators. A direct effect of ghrelin on the gastrointestinal oscillator has not yet been demonstrated in vivo or in vitro in fishes.…”
Section: :3mentioning
confidence: 99%
“…It was the first report on the identification of a GHSR-1b transcript from species other than mammals and the demonstration that receptor interaction might provide a possible explanation for the existence and biological significance of the sbGHSR-1b transcript. Since then GHS-R has also been identified in the zebrafish Danio rerio (Olsson et al, 2008), orange-spotted grouper Epinephelus coioides (Chen et al, 2008), channel catfish Ictalurus punctatus (Small et al, 2009), rainbow trout Oncorhynchus mykiss (Kaiya et al, 2009a), Mozambique tilapia Oreochromis mossambicus (Kaiya et al, 2009b), goldfish Carassius auratus (Kaiya et al, 2010) and Atlantic salmon Salmo salar (Hevrøy et al, 2011).…”
Section: Introductionmentioning
confidence: 99%